Multiple-fault-Tolerant strategy for three-phase hybrid active neutral point clamped converters using enhanced space vector modulation technique - Halabi, Laith M.; Alsofyani, Ibrahim Mohd; Lee, Kyo Beum (IEEE Access, 2020)
In recent decades, renewable energy has become an important part of the power generation field. In any renewable energy system, power converters form the dominant part, owing to their important role. However, such converters are exposed to the danger of single and/or multiple open-and short-circuit faults. This paper proposes a creative control strategy for tolerating the faults by generating a new switching sequence and reference signals in hybrid active natural point clamped (ANPC) converters. The hybrid ANPC convertors are exposed to consequent short-or open-circuit faults simultaneously for each kind of faults. In these regards, the operation under multi-short-circuit and multi-open-circuit faults are analyzed and described. Correspondingly, the control strategy with the selection of new vectors under the faulty conditions is explained and clarified in detail. Furthermore, the proposed strategy does not require installing any additional devices or changing the original topology, and it can be applied to hybrid ANPC converters without any special requirements to withstand high voltage levels. The effectiveness of the proposed control strategy is verified and confirmed by simulation results and experimentally tested using a 15-kW hybrid ANPC prototype converter.
Keywords: Active neutral point clamped; Control strategies; High voltage level; Open circuit faults; Prototype converter; Renewable energy systems; Short-circuit fault; Space Vector Modulation; Fault tolerance; hybrid ANPC; multiple faults; open circuit; short circuit